BLOOD SUGAR EXAMINATION AS EARLY DETECTION OF DIABETES MELLITUS IN COMMUNITIES KUTHI, SUMURGUNG, TUBAN - suhartono suhartono; Karyo; Tri Yunita Fitria Damayanti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Hyperglycemia is a state of increased blood glucose levels above 200 mg/dl and is an early symptom of diabetes mellitus (DM). Hyperglycemia is caused by a lack of insulin in the body. Diabetes Mellitus is a disease characterized by hyperglycemia and impaired metabolism of carbohydrates, fats and proteins associated with absolute or relative deficiencies in insulin action and/or secretion. The purpose of this study was to find out if there is a relationship between high blood sugar levels and the incidence of diabetes in Dusun Kuthi residents. Sumurgung. The type of research used was by going directly to the RW 08 community. Sampling was done by random sampling, namely changing the criteria from